Analisis Efisiensi, Elastisitas, Kontribusi dan Tren Pemungutan Pajak Air Permukaan Dalam Meningkatkan Penerimaan Pajak Daerah Provinsi Kalimantan - Audia, Devi Raisatul; Saleh, Muhammad (PPJP ULM, 2023)
The purpose of this study is to (1) determine the level of efficiency of the surface water tax in South Kalimantan Province (2) to determine the level of elasticity of the surface water tax to the regional tax of South Kalimantan Province (3) to determine the contribution of the surface water tax to the regional tax of South Kalimantan Province (4) to know the trend of surface water tax in South Kalimantan Province. The data used is secondary data from 2010 to 2020. The method used is descriptive quantitative method. The result of this research is that the efficiency of surface water tax in South Kalimantan Province has an average of 27.12% which is categorized as less efficient. For the calculation of the elasticity of the surface water tax, South Kalimantan Province has an average of less than 1, which is 0.25 which is inelastic, then the calculation of the contribution of the surface water tax in South Kalimantan Province has an average of 0.13% which means it is still very less contributing, while the trend The surface water tax of South Kalimantan Province for 2021 is predicted to be IDR 3,419,327,860 and in 2022 it is predicted to be IDR 3,537,945,393 and so on until 2025 it is predicted to be IDR 3,893,797,992.